(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article there are considered the problems of interfaith tolerance, associated with the need to improve interreligious harmony, mutual respect, prevention and avoidance of conﬂ icts on religious grounds. In solving these problems noted the initiative of President N.A.. Nazarbayev on carrying out in Kazakhstan of the Congress of leaders of world and traditional religions. Disclosed the role of the joint cooperation and exchange of experiences of the participants of the Congress in the face of eminent persons religions, well-known theologians, politicians and public ﬁ gures in the establishment of peace and stability in Kazakhstan society. Keywords: religion, peace, religious tolerance, good, faith, justice.